Phytochemical study and pharmacological activity of the schoutenia ovata korth. stems from the hills of Tulungagung - Setyowati, Eni; Agustin, Haslinda Yasti (Institute of Computer Science (IOCS), 2025)
Schoutenia ovata Korth. has a shrub or tree habit and is able to grow up to a height of 25 meters. Humans often use this plant as medicine, one of which is found on the stems. However, no one has researched the good phytochemical content of this plant stem. This is evident in the PubChem data, which indicates that there is no phytochemical profile available for this plant. Therefore, this study aims to determine the phytochemical content and pharmacological activity of Schoutenia ovata Korth. stems. The sample in this study is a stem taken from the hills of Tulungagung, East Java, Indonesia. The sample is then dried and made into a coarse powder. The content of chemical elements is analyzed using an X-ray fluorescence spectrometer. Furthermore, phytochemical tests are conducted to identify the presence of flavonoids, alkaloids, steroids, tannins, saponins, and phenols using the LC-MS/MS QTOF method. Pharmacological activities are investigated through a literature study. The Schoutenia ovata Korth. stems contain chemical elements O (48.6%), C (47%), K (2.9%), Ca (0.6%), Al (0.2%), Si (0.2%), P (0.2%), Cl (0.2%), Mg (0.1%). The results of phytochemical tests show that the stem contains alkaloids, flavonoids, and steroids. Based on the content of phytochemical compounds, the stems of Schoutenia ovata Korth. exhibits pharmacological activities, including antidiabetic, analgesic, anti-inflammatory, antioxidant, immunomodulatory, anticancer, and wound-healing properties.